RCQ, IMC AND CORPORAL FAT (%G) OF PROFESSIONAL PLAYERS OF SOCCER OF SÁ UNIVERSITY ESTÁCIO - 2ª DIVISION OF THE STATE CHAMPIONSHIP OF RIO DE JANEIRO (Fiep Bulletin - online, 2015)
Gift in 205 countries, the soccer to the long one of its existence conquered the affection of millions of people gifts in all continents, for being a simple of being practice and economically accessible sport any citizen. Each "Pantry of the World", carried through championships and matches, this sport became sufficiently competitive, the balance enters the teams during a competition stimulated the search for equalize. Objective: to get values that if they relate to the Index of Corporal Mass (IMC), Relation Waist Hip (RCQ) and Percentage of Corporal Fat (%G) of divided football players in five position: goalkeeper, back, lateral, half-field and forward. Methodology: Description data-collecting type the sample was composed for 31 professional football players of the University Estácio de Sá of the Second Division of the Championship of the State of Rio De Janeiro, being all of the masculine sort with average of age of 22,56 ± 1,88 years, For the application of the tests was used the following one to material: For perimeters a metallic metric ribbon SANNY® was used, for cutaneous folds, a science compass CESCORF®, for corporal mass, a scale mechanics FILIZOLA®, for stature, one science estadiômetro SANNY®, for calculates it of the IMC was used formulates it of Quetelet (1957), for the RCQ it formulates it of Bray & Gray(1988)e for % of fat formulates it of Petroski. Results :.As you measured of the results had been for forwards 7,58 G%, 23,48 IMC, 0,88 RCQ, for Goalkeepers 4,72 G%, 21,67 IMC, 0, 80 RCQ, Laterals 6,80 G%, 22,90 IMC, 0,84 RCQ, Half-fields 8,04 G%, 23,60 IMC, 0,85 RCQ, Backs 7,70 G%, 23,29 IMC, 0,86 RCQ. Conclusions: after it analyzes of the results, it is perceived that the half-field players had possessed a bigger index of IMC and %G, These values must, for being these athletes, responsible for the linking of the defense for the attack, during a departure, being necessary a bigger aerobic activity which had its permanent request, then needing a greater %G as energy source. Observing still that exactly with bigger indices, its RCQ was minor who the forwards, characterizing a lesser risk of coronary illnesses.
Keywords: Soccer; IMC; RCQ; % of corporal fat .